1985
DOI: 10.1037/0096-3445.114.1.25
|View full text |Cite
|
Sign up to set email alerts
|

On consciousness in syntactic learning and judgment: A reply to Reber, Allen, and Regan.

Abstract: In this article we examine Reber, Allen, and Regan's (1985) commentary on our analysis of consciousness and abstraction in a case of syntactical learning and judgment (Dulany, Carlson, & Dewey, 1984). We reject their methodological criticism; it is not recall, but assessment at the moment of judgment, that maximizes the validity of reports of rules in consciousness at many moments of judgment. Furthermore, as our computer simulations show, if subjects' reports were merely guessed justifications of unconsciousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
64
0
4

Year Published

1988
1988
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(69 citation statements)
references
References 32 publications
1
64
0
4
Order By: Relevance
“…The character of the debate over awareness was similar in several related research areas. After an initial report in which healthy participants exhibited learning while reporting that they were unaware of what they had learned (e.g., Nissen & Bullemer, 1987;Reber, 1967), subsequent research suggested other methods of interrogating awareness that seemed to reveal some conscious knowledge (e.g., Perruchet & Amorim, 1992;Dulany, Carlson, & Dewey, 1985). Resolving this issue appeared to depend on proving ''null awareness'' of acquired knowledge in healthy participants, which is clearly a daunting proposition (Merikle, 1994).…”
Section: Introductionmentioning
confidence: 94%
“…The character of the debate over awareness was similar in several related research areas. After an initial report in which healthy participants exhibited learning while reporting that they were unaware of what they had learned (e.g., Nissen & Bullemer, 1987;Reber, 1967), subsequent research suggested other methods of interrogating awareness that seemed to reveal some conscious knowledge (e.g., Perruchet & Amorim, 1992;Dulany, Carlson, & Dewey, 1985). Resolving this issue appeared to depend on proving ''null awareness'' of acquired knowledge in healthy participants, which is clearly a daunting proposition (Merikle, 1994).…”
Section: Introductionmentioning
confidence: 94%
“…Though their experimental results roughly replicated Reber’s, they concluded that implicitly instructed subjects showed no more learning than those explicitly instructed; moreover, according to them, the learning verified in the former could be accounted for by the subjects’ consciously learning the rules, namely by acquiring correlated grammars. A controversy ensued over methodology rather than over the distinction between conscious and unconscious knowledge (Brody, 1989; Dulany, Carlson, & Dewey, 1985; Reber, Allen, & Regan, 1985). …”
Section: History and Current Theories And Trendsmentioning
confidence: 99%
“…For instance, in a typical artificial grammar learning experiment, participants may judge the grammaticality of novel symbol strings on the basis of their similarity to stored exemplar strings or on the basis of the "chunk overlap" between training and test strings (e.g., Dulany, Carlson, & Dewey, 1985;Knowlton & Squire, 1994;Meulemans & van der Linden, 1997;Perruchet & Pacteau, 1990;Vokey & Brooks, 1992).…”
mentioning
confidence: 99%